VALIDASI KLINIK GENERAL HEALTH QUESTIONNAIRE-12: SEBAGAI INSTRUMEN SKRINING GANGGUAN KECEMASAN MENYELURUH DI PUSKESMAS - , EMELDAH; , Rahmat Hidayat, S.Psi, M.Sc, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mental health is a very important health care issue. The study from World Health Organization (WHO) found that mental disorder was suffered by approximately 25% of the population. Mental and behavioral disorders were also found in patients in primary health care services such as sub-district health center (Puskesmas), one of the public health services in Indonesia. Approximately 20-36% from the patients who went to the public health services were suffering from mental health problems. Several studies have shown that the physicians in public health services were difficult to diagnose those disorders. The aim from this research was to adapt and validate the General Health Questionaire-12 (GHQ â 12), a screening instrument to measure anxiety in sub-district health center as a primary health care. General Health Questionaire-12 (GHQ- 12) was used as the primary measurement instrument and the Structural Clinical Interview Diagnosis (SCID) as a diagnosis golden standard. The participants were 243 respondents in 25 sub-district health centers in Sleman and Yogyakarta. Likelihood ratio was used to compare the results between the GHQ and the SCID. The study stated that GHQ-12 appeared to be useful instrument to identify mental health problems, especially patient with generalized anxiety disorder.